Awareness, knowledge and perception of working adults towards vape - Ismail, Isma Anati (2016)
Vape is being increasingly used in Malaysia. Its works by heating a solution that contains flavourings and delivery system like propylene glycol. They may or may not contain nicotine and being marketed as a smoking cessation aid. Awareness of vape and perception is important as little is known about vape and public opinion towards it. Some people believe that vape can be less harmful than traditional cigarettes. There are limited study on awareness, knowledge and perception of vape in Malaysia. This study aimed to identify the prevalence of awareness, knowledge level, and perception of vape among working adults in UiTM Puncak Alam Campus. A cross-sectional study using questionnaire was conducted between May and June 2016 among working adults in UiTM Puncak Alam Campus aged 24-64 years (n=117). The questionnaires were available in two languages; Malay and English. We assessed the awareness, knowledge and perception about harmfulness among working adults. Data analyses were performed in June 2016. Overall, 87.2% of respondents were aware of vape. Adults aged 30-39 years, female and high education level were more likely to be aware of vape. When asked about the general knowledge of vape, most of the respondents have high knowledge level (44.4%). Of these, 82.4% believed that vape can be more harmful than traditional cigarettes and 80.4% agreed that vape should be banned in public areas such as cafe and restaurants. The perception that vape are harmful was more prevalent than the perception that vape are useful for smoking cessation aid. In conclusion, the prevalence of awareness of vape were high among working adults. A considerable level of knowledge about vape is found among working adults aged 30-39 years. Vape were perceived as more harmful than traditional cigarettes and not be effective as a smoking cessation aid. There should be increase in the advertisements and messages about the vape regarding the scientific evidence on the use and harmful effects in order to avoid creating mistaken ideas about their use.